IBM SmartCloud Essentials. - Schouten, Edwin (Packt Publishing, 2013)
A practical, user-friendly guide that provides an introduction to cloud computing using IBM SmartCloud, along with a thorough understanding of resource management in a cloud environment. This book is great for anyone who wants to get a grasp of what cloud computing is and what IBM SmartCloud has to offer. If you are an IT specialist, IT architect, system administrator, or a developer who wants to thoroughly understand the cloud computing resource model, this book is ideal for you. No prior knowledge of cloud computing is expected.